Age‐Related Long‐Term Longitudinal Changes in Left Ventricular Mechanical Function in Breast Cancer Patients Undergoing Anthracycline and Trastuzumab Treatment - Begimai Akbalaeva; Priti Singh; Salman Khan (Clinical Case Reports)
ABSTRACT Age significantly influences the severity of chemotherapy‐induced cardiotoxicity (cardiotoxicity) in HER2‐positive breast cancer patients. Comprehensive cardiac monitoring before, during, and after anthracycline and trastuzumab regimens is essential. Tailored assessments can help identify vulnerable patients, optimize treatment, and mitigate risks of heart complications while maintaining therapy efficacy.